Poor response to oral indomethacin therapy for persistent ductus arteriosus in very low birthweight infants. - Cooke, R W (1979)
Administration of oral indomethacin to treat cardiorespiratory failure in 7 low birthweight infants, after failure of conventional therapy, produced an improvement in only 2 infants. These infants had a higher birthweight than the group as a whole. Surgical ligation, rather than oral indomethacin, may be the treatment of choice for persistent ductus arteriosus in very low birthweight infants.